Integrating Maqasid al-Shariah and Sustainable Development Goals Islamic Financial Planning: A Framework for Ethical Wealth Distribution - Syaichoni, Ahmad; Huda, Qomarul; Pangestu, Nana; Sampurno, Rama Wahyu (Department of Islamic Financial Management, Faculty of Economics and Islamic Business, Sunan Kalijaga State Islamic University, Yogyakarta, Indonesia., 2025)
Background: The global financial system faces escalating challenges in reconciling ethical wealth distribution with sustainable development, particularly within Islamic economies. Despite the shared emphasis of Maqasid al-Shariah (objectives of Islamic law) and the Sustainable Development Goals (SDGs) on justice, equity, and environmental stewardship, their integration remains fragmented. Islamic financial institutions (IFIs) often prioritize Shariah compliance over proactive contributions to sustainability, while regulatory fragmentation and gender-environment gaps hinder systemic progress. Objectives: This study aims to: (1) analyze the structural alignment between Maqasid al-Shariah and SDGs in Islamic financial planning, (2) identify systemic barriers to their integration, and (3) propose actionable strategies to optimize Islamic finance’s role in ethical wealth distribution. Novelty: The research fills critical gaps in Islamic academic discourse by: Introducing the Maqasid-SDG Integration Theory, which recontextualizes classical Islamic jurisprudence within modern sustainability frameworks. Developing a Maqasid-SDG Index to evaluate financial products’ socio environmental impact, addressing the absence of standardized metrics. Resolving debates on adaptive jurisprudence (e.g., redefining daruriyyat to include climate action) and gender inclusivity in Islamic finance. Research Methodology / Design: A mixed-methods sequential explanatory design was employed, combining Qualitative Analysis: Thematic coding of classical texts (e.g., al-Shatibi’s Al-Muwafaqat), 45 semi-structured interviews with Shariah scholars and policymakers, and case studies of Malaysia and Indonesia. Quantitative Analysis: PLS-SEM modeling of secondary data from 30 IFIs (2015–2023) and regression analysis of SDG progress metrics (e.g., poverty rates, CO2 emissions). Comparative Jurisprudence: Cross-referencing Hanafi, Maliki, Shafi’i, and Hanbali interpretations of wealth distribution ethics. Findings: SDG Alignment: Shariah-compliant mechanisms like Zakat and green Sukuk reduced povertyby 12.7% and emissions by 2.3 million metric tons annually, respectively (β = 0.42, p < 0.01). Institutional Barriers: Regulatory fragmentation limited SDG-aligned financing to 28% in GCC countries versus 64% in Malaysia. Gender disparities persisted, with only 12% of Islamic banks offering women centric products. Theoretical Advancements: The Maqasid-SDG Index revealed a 63% explanatory power (R² = 0.63) for ethical outcomes, while juristic reinterpretations of maslaha (public interest) enabled blockchain-based Sukuk innovations. Implication: Theoretical: The study bridges Islamic ethics with sustainability science, offering a dynamic framework for adaptive jurisprudence. Practical: Policymakers should prioritize (1) cross-border regulatory harmonization, (2) financial literacy campaigns, and (3) gender-environment nexus products (e.g., Takaful for women-led green enterprises). Policy: Centralized Shariah governance, as seen in Malaysia’s Value-Based Intermediation framework, enhances SDG alignment but requires balancing with grassroots inclusivity (r= -0.58).